How I do it: Endoscopic endonasal resection of the medial wall of the cavernous sinus - Ruiz-Valdepeñas, Eugenio Cárdenas; Ruiz, Estrella Barrero; Cancela, Aberto Acitores; Berrocal, Victor Rodriguez (Acta neurochirurgica, 2024)
Background Resection of the medial wall of the cavernous sinus (MWCSR) is a growing surgical maneuver for the radical removal of pituitary adenomas. Method We present a simple modification of the technique following the two dural layers of the floor of the sella turcica, allowing for early identification of the medial wall and simplifying dissection. We support this technique with an anatomical analysis on cadaveric specimens and clarifying dissection images. Conclusion Recognition and dissection of the dural unfolding of the floor of the sella turcica are "key points" that lower the risk and facilitate the MWCSR.